PENGEMBANGAN MEDIA GAME INTERAKTIF ELEKTRONIK BERBASIS QUIZWHIZZER PADA SUBTEMA USAHA PELESTARIAN LINGKUNGAN - Lia Audina; Teti Rostikawati; Resyi A. Gani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the development and feasibility testing of QuizWhizzer-based Electronic Interactive Game media with the Sub-theme of An Attempt for Environmental Conservation at the fifthgrade students of SDN Cikutamahi 01. The method used is the Research and Development (R&D) with the ADDIE method (Analyzing, Designing, Developing, Implementing, and Evaluating). To find out the feasibility of QuizWhizzer-based Electronic Interactive game media, the researchers provided validation for 6 experts, trials, and field trials. The results indicate that the QuizWhizzer-based Electronic Interactive Game is feasible to use as an evaluation in the classroom. Based on the data validation, the media expert validation average percentage was 92%, the linguist validation average percentage was 100%, and the material expert validation average percentage was 98.33%. In addition, the results of the small group trial obtained 81.33%, and the data from the field trial obtained 95.23% in the